An Overview of Risk Factors Influencing Severity Levels of Dental Caries in Public Islamic Elementary School Students in an Endemic Leprosy-Populated Village in East Java - Ramadhani, Aulia; Khafid, M.; Daruanggono, Dicky; Chotimah, Chusnul; Arisetiawan, M. Taufik; Metikasari, Nur Indah; Irawan, Revinska Bagus; RHP, Annisa Galuh; Sarilaksmi, Nastiti; Y, Rizki Widyakartika; Arijati, Dinar; Iffatuz, Haninda (Indonesian Journal of Dental Medicine, 2020)
Background: Dental caries is the destruction of hard tissues of the teeth due to activities of bacteria that change food debris, especially sugar and starch into acid and then demineralize the teeth. Dental caries is a common infection affecting mostly schoolchildren as they usually consume snacks at schools and rarely have mineral water after. Based on the research, 28.5% of children in the age of 5-9 years and 25.2% of children in the age of 10-14 years have oral health problems. Purpose: This study assessed the risk factors influencing the severity levels of dental caries. Methods: This study was observational descriptive research using a cross-sectional approach. The samples used in this study were 118 students selected through stratified proportional random sampling. Data were collected through interviews, intra-oral examination, and school data observation. All data collected were analyzed using cross-tabulation and odds ratio with the SPSS program. Results: As many as 68.6% of the respondents had highly severe dental caries (dmf-t>3). The value of theodds ratio between the severity of caries and oral hygiene status was 5.63. While the value of the odds ratio between the severity of caries and water drinking after snacking was 1.89. The odds ratio tests showed oral hygiene status and water drinking after snacking were the risk factors of caries. Conclusion: Age, gender, parent's knowledge, parent's occupation, snacking habit, teeth-brushing habit, water drinking habit, and oral hygiene status were the risk factors influencing the severity levels of dental caries.